Caries and fluoridated water in two Brazilian municipalities with low prevalence of the disease - Mariângela Guanaes Bortolo da Cruz; Paulo Capel Narvai (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To analyze the association between exposure to fluoridated water and dental caries in a context of widespread use of fluoride toothpaste in Brazil, in a scenario of low prevalence of the disease. METHODS This is a cross-sectional observational study, of the census type, in the form of a double population-based epidemiological survey carried out in two municipalities of the state of São Paulo in 2014. The sample consisted of adolescents aged 11 and 12 years, exposed (n = 184) or not exposed (n = 128) to fluoridated water for at least five years. The populations studied lived in communities of the same geographic region and had small demographic size and similar socioeconomic classification, differing only in the exposure (Silveiras) or not exposure (São José do Barreiro) to fluoridated water. The experience, magnitude, and degree of polarization of dental caries in these populations were analyzed using the DMFT and SiC indexes, and the association was tested using Pearson's chi-square statistics and prevalence ratio between those not exposed and those exposed to fluoridated water. RESULTS Although caries experience (DMFT ≥ 1) was not associated with exposure to fluoridated water (chi-square = 1.78; p = 0.18; α = 5%), a significant difference was observed in the magnitude with which the disease reached the population: the means of DMFT were 1.76 in those exposed and 2.60 in those not exposed and the means of SiC were 4.04 and 6.16, respectively. The degree of polarization, indicated by the percentage of subjects with DMFT = 0, was different, being it higher (41.8%) in subjects exposed and lower (34.3%) in subjects not exposed. The prevalence ratio between those not exposed and those exposed was 1.13, indicating little expressiveness in prevalence difference. CONCLUSIONS Exposure to fluoridated water implied lower mean values for the DMFT and SiC indexes, even in the presence of the concomitant exposure to fluoridated toothpaste, in a scenario of low prevalence of the disease, and with a similar pattern of caries distribution in the populations analyzed.